Program motion of unloading manipulators - Binh, Vu Duc; Do Dang Khoa; Phan Dang Phong; Do Sanh (Vietnam Journal of Science and Technology, 2018)
In the paper, the program motion of an unloading manipulator which is treated as a first integral of the considered system, is investigated. Currently, the popular way to solve such problem is the method of Lagrange multipliers. In the paper, the authors use another approach, the Priciple of Compatibility, in which the required program is treated as one of motion equations of the system. In the particular case, the program is considered as one of first integrals of the system. For illustrating the proposed method, the motion of an unloading manipulator of three degrees of freedom is considered